Do attendees at sexual health and HIV clinics prefer to be called in by name or number?. (June 2014) - Dabis, R; Nightingale, P; Kumar, V; Jaffer, K; Radcliffe, K
Calling patients in from the waiting area is an important aspect of the initial medical encounter. According to national and international guidelines, clinics should decide on an appropriate way of calling patients in from the waiting room for consultations; however, no preference is actually recommended. A survey was carried out to see if patients were happy to be called in by number, first name, surname, full name, or title (Mr/Mrs/Miss/Ms) followed by surname. One hundred unselected patients were drawn from each clinic including; a genito-urinary medicine (GUM), a co-located GUM (cGUM) and co-located reproductive health (cRH), an HIV and a reproductive health (RH) clinic. Patients from the GUM, cGUM, cRH and RH clinics preferred to be called in by number rather than full name or title. Patients from the cRH clinic also preferred number to first name. In contrast, patients from the HIV clinics preferred to be called in by first name rather than number, surname, full name or title. Following this survey it would appear that number would be the most popular method of calling patients in sexual and reproductive health clinics and first name is the choice in HIV clinics.